2020
DOI: 10.3390/rs12182880
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Comparison of Remotely Sensed Sea Ice Concentration Products with ERA-Interim Reanalysis Data in Polar Regions

Abstract: Sea ice concentration (SIC) plays a significant role in climate change research and ship’s navigation in polar regions. Satellite-based SIC products have become increasingly abundant in recent years; however, the uncertainty of these products still exists and needs to be further investigated. To comprehensively evaluate the consistency of the SIC derived from different SIC algorithms in long time series and the whole polar regions, we compared four passive microwave (PM) satellite SIC products with the ERA-Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…The accuracies of SIC algorithms under different net ice surface fractions (ISFs, i.e., fraction of the ice surface excluding melt pond and open water) [6], [9], the impacts on truncated 100% SIC and the performances of weather filters [7], [8] were also studied. Studies have shown that the uncertainties of PM SICs tend to be larger near ice edges and during summer melting periods [11], [12], [13], [14], [15], which is up to 20%-40% [6]. This is mainly due to the limitation of algorithm and the variable radiometric characteristics of sea ice under such conditions.…”
mentioning
confidence: 99%
“…The accuracies of SIC algorithms under different net ice surface fractions (ISFs, i.e., fraction of the ice surface excluding melt pond and open water) [6], [9], the impacts on truncated 100% SIC and the performances of weather filters [7], [8] were also studied. Studies have shown that the uncertainties of PM SICs tend to be larger near ice edges and during summer melting periods [11], [12], [13], [14], [15], which is up to 20%-40% [6]. This is mainly due to the limitation of algorithm and the variable radiometric characteristics of sea ice under such conditions.…”
mentioning
confidence: 99%